The Roles of Social Status, Maternal Stress, and Parental Investment in Modulation of Hypothalamic-Pituitary-Interrenal Axis Function in Teleost Fish - Jeffrey, Jennifer D (Université d'Ottawa / University of Ottawa, 2014)
In teleost fish, the main glucocorticoid stress hormone, cortisol, is released via the hypothalamic-pituitary-interrenal (HPI) axis. This thesis examined the premise that social status, maternal experience, and reproductive status affect HPI axis function in fish. Social stress in juvenile rainbow trout (Oncorhynchus mykiss) chronically elevates circulating cortisol levels. In this thesis, social subordinance as well as exogenous cortisol treatment resulted in decreased plasma adrenocorticotropic hormone (ACTH) levels, consistent with a negative feedback role of cortisol in modulating HPI axis activity. At the target tissue level, liver glucocorticoid receptor 2 (GR2) mRNA and total GR protein levels were lower in subordinate fish. Although subordinate fish exhibited elevated resting cortisol levels, cortisol and glucose responses to an acute stressor were attenuated. Using an in vitro head kidney preparation, this attenuated cortisol response was attributed to lower ACTH-stimulated production of cortisol. By contrast, dominant status regulated genes associated with cortisol biosynthesis. The consequences of maternal social status on offspring HPI axis function were investigated in zebrafish (Danio rerio). At 48 hours post-fertilization (hpf), when de novo cortisol synthesis becomes possible, larvae of dominant females exhibited lower baseline cortisol levels accompanied by lower mRNA levels of corticotropin-releasing factor and cytochrome P450 side chain cleavage enzyme. Offspring of subordinate females exhibited attenuated stress-induced levels of cortisol at 144 hpf, perhaps as an adaptive response to maternal stress experience. Finally, modulation of HPI axis function was explored as a mechanism underlying attenuation of the stress response during early paternal care in smallmouth bass (Micropterus dolomieu). In response to a stressor, males guarding free-swimming fry but not eggs elevated plasma ACTH and cortisol as well as mRNA levels of key HPI axis genes. These results point to a hypoactive HPI axis in males during early parental care as a mechanism for resistance to stress in these fish. Collectively, the results of this thesis emphasize the adaptive plasticity of the HPI axis. Activity of the HPI axis in teleost fish can be modulated by the individual’s experience (e.g., social status) or circumstances (e.g., parental care), as well as by maternal stress.
Keywords: fish; stress; social status; maternal stress; parental care; physiology